Involvement of children in hands-on meal preparation and the associated nutrition outcomes: a scoping review - Choon, Ming Ng; Kaur, Satvinder; Hui, Chin Koo; Firdaus, Mukhtar (Wiley-Blackwell Publishing, 2021)
Background: Emerging research has explored hands-on meal preparation as a strategy to improve children's nutrition-related outcomes. This scoping review was conducted to describe the extent of studies on children's involvement in hands-on meal preparation and the related psychosocial outcomes, actual nutrition behaviour/food consumption and weight status. Methods: Scoping review methodology was used to select relevant studies, as well as extract and collate the data. Four databases (PubMed, Google Scholar, Science Direct and Cochrane Database of Systematic Reviews) were searched from the earliest available time up to December 2020. Observational studies, experimental studies and reviews that were conducted among children aged 5–12 years old and published from 2010 to 2020 were retrieved. Studies extracted involved children in hands-on healthy meal preparation activities and explored the associated nutrition outcomes. Results: In total, 28 studies (5 observational studies, 21 experimental studies, 2 reviews) were included in the final review. Studies conducted demonstrated improvement in children's psychosocial outcomes and actual nutrition behaviour/food consumption after participating in hands-on meal preparation activities, despite differences in methodology, programme content and settings (countries/cultural origins). Limited studies assessed children's nutrients intake and weight status. Conclusions: The current review suggests that hands-on meal preparation comprises approach for instilling positive perceptions towards nutrition/healthy foods, potentially improving children's diet. Future studies should include the assessment of nutrient intake and weight status. The long-term sustainability of these nutrition outcomes should be explored.